Unexpected Help: Follicular Regulatory T Cells in the Germinal Center - Xie, Markus M.; Dent, Alexander L. (Frontiers in Immunology, 2018)
Follicular helper T (Tfh) cells are necessary for germinal center (GC) formation and within the GC, provide key signals to B cells for their differentiation into plasmablasts and plasma cells that secrete high-affinity and isotype-switched antibody (Ab). A specialized subset of Foxp3+ T cells termed T follicular regulatory (Tfr) cells, also regulate the differentiation of Ab-secreting cells from the GC. Tfr-cell function in the GC is not well understood, however the dominant paradigm currently is that Tfr cells repress excessive Tfh and GC B cell proliferation and help promote stringent selection of high affinity B cells. A mouse model where the Bcl6 gene is specifically deleted in Foxp3+ T cells (Bcl6FC mice) allows the study of Tfr cell function with more precision than other approaches. Studies with this model have shown that Tfr cells play a key role in maintaining GC B cell proliferation and Ab levels. Part of the mechanism for this positive “helper” effect of Tfr cells on the GC is Tfr cell-derived IL-10, which can promote B cell growth and entry into the dark zone of the GC. Recent studies on Tfr cells support a new paradigm for Tfr cell function in the GC reaction. Here we review studies on Tfr cell functions and discuss the evidence that Tfr cells can have a major helper role in the GC-dependent Ab response.